From habits of attrition to modes of inclusion: enhancing the role of private practitioners in routine disease surveillance - Phalkey, Revati (BMC health services research, 2017)
Private practitioners are the preferred first point of care in a majority of low and middle-income countries and in this position, best placed for the surveillance of diseases. However their contribution to routine surveillance data is marginal. This systematic review aims to explore evidence with regards to the role, contribution, and involvement of private practitioners in routine disease data notification. We examined the factors that determine the inclusion of, and the participation thereof of private practitioners in disease surveillance activities.
Gesehen am 26.09.2018